2019
DOI: 10.1371/journal.pone.0221770
|View full text |Cite
|
Sign up to set email alerts
|

The Pacific harbor seal gut microbiota in Mexico: Its relationship with diet and functional inferences

Abstract: Diet is a primary driver of the composition of gut microbiota and is considered one of the main routes of microbial colonization. Prey identification is fundamental for correlating the diet with the presence of particular microbial groups. The present study examined how diet influenced the composition and function of the gut microbiota of the Pacific harbor seal ( Phoca vitulina richardii ) in order to better understand the role of prey consumption in shaping its microbiota. This species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 69 publications
4
37
1
Order By: Relevance
“…This is supported by observations of higher prevalence of Firmicutes compared to Proteobacteria in salinity gradients [30]. Increased incidence of Firmicutes has also been related to the consumption of the Engraulidae fish [31] that M. vivesi consumes [32], due to their high content of polyunsaturated fatty acids that are known to promote intestinal enrichment of Firmicutes [33]. Furthermore, Photobacterium are ubiquitous in the oceans [34] and often found in symbiotic relationships with fish within the dietary spectrum of M. vivesi [35,36].…”
Section: Piscivorous Bats Host Unique Gut Microbiotasmentioning
confidence: 52%
“…This is supported by observations of higher prevalence of Firmicutes compared to Proteobacteria in salinity gradients [30]. Increased incidence of Firmicutes has also been related to the consumption of the Engraulidae fish [31] that M. vivesi consumes [32], due to their high content of polyunsaturated fatty acids that are known to promote intestinal enrichment of Firmicutes [33]. Furthermore, Photobacterium are ubiquitous in the oceans [34] and often found in symbiotic relationships with fish within the dietary spectrum of M. vivesi [35,36].…”
Section: Piscivorous Bats Host Unique Gut Microbiotasmentioning
confidence: 52%
“…Of the three mussel species that exhibited functional redundancy ( O. unicolor , E. arca , and C. asperata ), each had significant year-to-year variation in the relative abundances of three abundant bacterial families (Fusobacteriaceae, Planctomycetaceae, and Clostridiaceae). Each of these families was also abundant in previously published microbiomes that also exhibited functional redundancy [ 43 , 44 , 45 ]. The apparent functional redundancy may result in increased functional stability and resilience against not only naturally fluctuating conditions but also anthropogenic disturbances [ 46 ].…”
Section: Discussionmentioning
confidence: 98%
“…Some researchers have indicated that host habitat, diet, and phylogeny all contribute to variations in the gut microbial composition of marine mammals (Bik et al 2016). Recently, high-throughput sequencing technology has facilitated the study of gut microbiomes in different marine mammals, such as seals (Pacheco-Sandoval et al 2019), sea lions (Lavery et al 2012), and manatees (Merson et al 2014). However, challenges in the sampling of some marine mammals, especially cetaceans, have resulted in limited information on gut microbiome diversity.…”
Section: Introductionmentioning
confidence: 99%